Cybercrime and social assistance analyzing scam tactics and developing countermeasures case study of developing country zambia - Mweemba, Lavu (Proceedings of International Conference for ICT (ICICT) - Zambia, 2025)
This dissertation investigates the increasing prevalence of cybercrime scams targeting social assistance beneficiaries in Zambia, a concern that poses significant risks to vulnerable populations reliant on healthcare and social support systems. The research identifies specific tactics employed by scammers, such as phishing, social engineering, and impersonation, while revealing systemic vulnerabilities exacerbated by inadequate protective measures and a general lack of awareness among citizens. By employing a mixed-methods approach, including qualitative and quantitative data collection through surveys, interviews, and case analyses, the study uncovers critical insights into the demographics most affected by these scams and the psychological impacts they endure. Findings indicate that a considerable proportion of beneficiaries remain uninformed about existing protections, leading to increased susceptibility to fraud. The implications of this research are profound, as it sheds light on the urgent need for targeted educational initiatives and the enhancement of cyber security protocols within social assistance frameworks. The study not only contributes to the existing literature on cybercrime and social welfare but also suggests a model for bolstering the resilience of healthcare systems in developing countries. By addressing these vulnerabilities and implementing robust countermeasures, policymakers can mitigate the impact of cybercrime, ultimately protecting the health and well-being of at-risk populations